Andrographis Paniculata in the Treatment of Upper Respiratory Tract Infections - Annisa Septrina (Eureka Herba Indonesia, 2022)
Andrographis paniculata is a species of Andrographis paniculata (Burm. F) The herbaceous plant Nees, sometimes known as "king of bitters," is a member of the Acanthaceae family. It's commonly used to treat sore throats, flu, and upper respiratory tract infections in China, India, Thailand, and Malaysia. In numerous studies, andrographolide, a significant bioactive chemical ingredient of the plant, has shown anticancer potentialIn experimental models of asthma, stroke, and arthritis, andrographolide and its derivatives show anti-inflammatory properties. Pharmaceutical chemists have recently synthesized a number of andrographolide derivatives with important pharmacological properties such as anti-inflammatory, antibacterial, anticancer, antidiabetic, anti-HIV, antifeedant, and antiviral properties. The summary of the effects of andrographolide on cardiovascular illness, platelet activation, infertility, and NF-B activation in this research is remarkable. In traditional Indian and Chinese medicine, a variety of plant items were frequently recommended as medications. We investigate the potency of four selected phytochemicals from the A. paniculata plant, namely andrographolide (AGP1), 14-deoxy 11,12-didehydro andrographolide (AGP2), neoandrographolide (AGP3), and 14-deoxy andrographolide (AGP4), against four key targets, including three non-structural protein (3 L main protease (3CLpro), Papain like proteinase (PLpro) and RNA-directed RNA polymerase (RdRp)) and a structural protein (spike protein (S)) of the virus which are responsible for replication, transcription and host cell recognition. This paper intended to know the mechanism of A.Panniculata bioactive compounds and its effect to relief the upper respiratory tract infection symptomps.